长距离上运带式输送机张紧特性的研究和分析 - 董安; 潘宏侠; 龚明 (Jixie chuandong)
Aiming at modern coal mine product boost and requirement of the long range belt conveyor, through the quantitative analysis of steeply inclined belt conveyor, the engineering mechanical knowledge is applied to analyze the tension force of the belt conveyor, by using cosimulation software AMESim, the simulation of hydraulic tensioner of belt conveyor is carried out. According to the result, the hydraulic tensioner responses quickly to the belt conveyor start is obtained and the cushion equipment gets good effect on the strike.